2014
DOI: 10.2967/jnumed.113.129015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Hypoxia Imaging: Second-Generation Analogues of 64Cu-ATSM

Abstract: Myocardial hypoxia is an attractive target for diagnostic and prognostic imaging, but current approaches are insufficiently sensitive for clinical use. The PET tracer copper(II)-diacetyl-bis (N4-methylthiosemicarbazone) ( 64 Cu-ATSM) has promise, but its selectivity and sensitivity could be improved by structural modification. We have therefore evaluated a range of 64 Cu-ATSM analogs for imaging hypoxic myocardium. Methods: Isolated rat hearts (n 5 5/group) were perfused with normoxic buffer for 30 min and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…Hueting et al have recently suggested in this journal that the biodistribution and pharmacokinetics of 64 Cuacetate in tumor-bearing mice is similar to that of 64 Cu-ATSM when assessed after 2 or 16 h, and that 64 Cu-acetate exhibits hypoxia selectivity in cultured cancer cells, suggesting that 64 Cu-bis(thiosemicarbazone) complexes dissociate quickly in vivo and that the resultant biodistribution observed by PET is that of free copper, questioning the validity of 64 Cu-ATSM as a hypoxia tracer (34). We and other groups have observed no such nonspecific uptake of ionic 64 Cu 21 salts in normoxic or hypoxic myocytes in culture (15), CHO cells (35), or isolated buffer-perfused hearts (17,21). The wide variation in pharmacokinetics and early biodistributions that the different bis(thiosemicarbazones) have been shown to display, with some being hypoxia-selective (ATSM, ATS, CTS) and some not (pyruvaldehyde-bis(N4-methylthiosemicarbazone) [PTSM], glyoxal-bis(N4-methylthiosemicarbazone) [GTSM]), and with some crossing the blood-brain barrier (GTSM, PTSM, ATSM) and some not (ATS) (36,37), would also argue against a common nonselective mechanism of early tissue uptake.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Hueting et al have recently suggested in this journal that the biodistribution and pharmacokinetics of 64 Cuacetate in tumor-bearing mice is similar to that of 64 Cu-ATSM when assessed after 2 or 16 h, and that 64 Cu-acetate exhibits hypoxia selectivity in cultured cancer cells, suggesting that 64 Cu-bis(thiosemicarbazone) complexes dissociate quickly in vivo and that the resultant biodistribution observed by PET is that of free copper, questioning the validity of 64 Cu-ATSM as a hypoxia tracer (34). We and other groups have observed no such nonspecific uptake of ionic 64 Cu 21 salts in normoxic or hypoxic myocytes in culture (15), CHO cells (35), or isolated buffer-perfused hearts (17,21). The wide variation in pharmacokinetics and early biodistributions that the different bis(thiosemicarbazones) have been shown to display, with some being hypoxia-selective (ATSM, ATS, CTS) and some not (pyruvaldehyde-bis(N4-methylthiosemicarbazone) [PTSM], glyoxal-bis(N4-methylthiosemicarbazone) [GTSM]), and with some crossing the blood-brain barrier (GTSM, PTSM, ATSM) and some not (ATS) (36,37), would also argue against a common nonselective mechanism of early tissue uptake.…”
Section: Discussionmentioning
confidence: 80%
“…We recently demonstrated that 64 Cu-CTS and its analog 64 Cu-ATS exhibit significantly greater hypoxia selectivity than the current lead compound 64 Cu-ATSM in hearts perfused with hypoxic (0% O 2 ) buffer (17). Although this finding was a promising first step in the screening process, the key to the progression of this class of compounds is to identify complexes selective for levels of hypoxia that correlate with survivable (and treatable) cardiac disease (9,10).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations